The Prosperity Gospel in Africa: An African Pentecostal Hermeneutical Consideration - Nel, Marius (Wipf and Stock Publishers, 2020)
Africans’ prevailing interest in the prosperity gospel is not only connected to the influence of American prosperity teachers reaching a worldwide audience through their imaginative use of the media, but is also related to the African worldview and African traditional religion, and its lasting influence on contemporary Africans and the way they think about prosperity, as well as their interest in prosperity in post-colonial Africa. The research from a classical Pentecostal perspective about the impact of the prosperity message on Africa is necessary, timely, and relevant because of its influence in the African Pentecostal movement and its potential to harm the faith of believers, leading to the potential disillusionment of Christian believers who put their trust (and money) in formulas and recipes that seemingly only work for others, especially the prosperity leaders who lead by example with incredulous riches and wealth.
Keywords: Religion / Christian Church / General; Religion / Christian Theology / General; Religion / Christianity / Pentecostal & Charismatic